2023
DOI: 10.1177/15248380231160847
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women Who Sell Sex in Eastern and Southern Africa: A Scoping Review

Abstract: Women who sell sex (WSS) are vulnerable to violence. We present a scoping review of the last decade of research on the prevalence and incidence of, factors associated with, and services regarding violence against WSS in Eastern and Southern African (ESA). A systematic search of various databases resulted in 20 papers being reviewed. Inclusion criteria, applied by the first two authors, were as follows: empirical papers, key research problem is violence against WSS, and conducted in ESA countries. The lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…A scoping review of the previous ten years of research on the frequency and incidence of, variables linked to, and services-related violence in Eastern and Southern Africa found that the women who sell sex are vulnerable to violence (Macleod et al, 2024). The present study revealed diverse forms of sexual violence representing the forms of verbal aggressions to physical violence and abortion.…”
Section: Discussionmentioning
confidence: 60%
“…A scoping review of the previous ten years of research on the frequency and incidence of, variables linked to, and services-related violence in Eastern and Southern Africa found that the women who sell sex are vulnerable to violence (Macleod et al, 2024). The present study revealed diverse forms of sexual violence representing the forms of verbal aggressions to physical violence and abortion.…”
Section: Discussionmentioning
confidence: 60%